CP trajectory diagram - a tool for a pictorial representation of CP and matter effects in neutrino oscillations - Minakata, H.; Nunokawa, H. (Elsevier B.V., 2003)
We introduce a CP trajectory diagram in bi-probability space as a powerful tool for a pictorial representation of the genuine CP and the matter effects in neutrino oscillations. The existence of correlated ambiguity in the B is uncovered. The principles of tuning the beam energy for a determination of CP-violating phase delta and the sign of Deltam(13)(2) given baseline distance are proposed to resolve the ambiguity and to maximize the CP-odd effect. We finally point out, quite contrary to what is usually believed, that the ambiguity may be resolved with similar to 50% chance in the super-JHF experiment despite its relatively short baseline of 300 km. (C) 2003 Elsevier B.V. B.V. All rights reserved.